Remarriage strategies for post-disaster widows and widowers following the 2004 Indian Ocean tsunami in Aceh, Indonesia - Mahdi, Saiful (2023)
The 2004 Indian Ocean tsunami caused extensive loss of life and disrupted family units, leaving large numbers of widows, widowers, and orphans. While it is common to identify disaster widows and orphans as potentially vulnerable groups, there has been limited research about how families are reconstructed after a major disaster. The main objective of this paper is to better understand what factors motivate persons who lost a spouse in a disaster to either re-marry or stay single. We use quantitative data from a statistically representative survey of tsunami-affected households in the Banda Aceh, Aceh Besar, and Aceh Jaya districts in the Aceh province of Indonesia conducted a decade after the tsunami to show that 18% of households reported the death of a spouse during the tsunami. Out of these, 66% of widows/widowers reported marrying again within a decade after the tsunami, with most remarried within the first three years after the disaster. We use qualitative data from in-depth interviews with 36 widows and widowers to identify motivations behind the decision to remarry or stay single. We found that widows were most likely to get remarried to provide economic security, support for their surviving children, and because of concerns about their reputation if they were unmarried. Widowers were more likely to remarry to secure domestic support and caregiving for themselves as they got older and to help them care for their surviving children. Some widows and widowers decided not to remarry because of concerns about assuming additional financial liabilities, distressing their surviving children, and (for women) giving up personal freedoms. Our research on the re-marriage decisions of tsunami widows and widowers shows that very personal decisions about family should be seen within the framework of household and community resilience.